Hypoglycemic, antidiabetic and toxicological evaluation of leaf extract of Xylopia parviflora (A. rich.) Benth - Farouk Adedeji Oladoja; Emmanuel S. Irokosu; Elijah O. Oyinloye; Akanji A. Murtala; Marcus D. Ayoola; Aderonke A. Aderinola; Gift Crucifix Pender; Ololade A. Popoola (Elsevier, 2024)
Background: Almost all Xylopia species have a long history of being used therapeutically in China due to their potent antioxidant properties. Xylopia parviflora (X. parviflora) is a relatively novel plant comprised mainly of beta-pinene, which has a rich history in Chinese medicine and is a principal active constituent in numerous Chinese herbs such as Rakkyo, the Chinese onions, Huasi Baidu Fang and Ru Xiang which are all native to China. Objective: The study evaluated the antidiabetic potentials of the methanol leaf extract of X. parviflora and its toxicity profile. Methods: A modified version of the OECD guidelines was used to conduct acute and sub-chronic toxicity tests on the plant extract. The extract's effects on glucose, haematological, and biochemical components were evaluated using standard procedures. Using glibenclamide (10 mg/kg) and distilled water as positive and negative controls, the extract was tested for its antidiabetic activity in diabetic rats with streptozotocin induction at 50, 150, and 300 mg/kg for 28 days. Furthermore, vital organs underwent histopathological examination. Analysis of Variance (ANOVA) and the Dunnett multiple comparison tests were used for the statistical analysis, with a significance level of p < 0.05 Results: Preliminary phytochemical analysis of the leaf extract revealed the presence of tannins, flavonoids, saponins, alkaloids, terpenoids, deoxy-sugars, and anthraquinones. The extract's median lethal dose (LD50) was greater than 2000 mg/kg in mice. Although it significantly reduced blood glucose levels in normal rats at 150 and 300 mg/kg doses, it had no toxic effects on the haematological and biochemical components of the collected blood samples. The extract produced an antidiabetic, non-dose-dependent impact on day seven at all the tested doses in streptozotocin-induced rats. On days 14, 21, and 28, however, glibenclamide and extract activity at all tested doses were comparable. At 200 mg/kg, the extract did not affect the histology of the liver, brain, kidney, or pancreas, but at 400 and 800 mg/kg, it had a slight and severe impact on these organs, respectively. Conclusion: According to the study's findings, X. parviflora has antihyperglycemic activity and is non-toxic at low doses but may be harmful at high doses.